IDENTIFICATION OF STUDENTS WITH TALENT IN THE TECHNICAL DOMAINS - ANGHEL IONICA-ONA (Studia Universitatis Babes-Bolyai, 2013)
ABSTRACT. The technological evolution requires a constant innovative perspective and from this point of view innovation is the result of the creativity among the working and extremely gifted persons. There are the inventor engineers who actually have turned their potential technical talent into fact. in this paper we wish to synthesize generally the problem of the identification of gifted and talented people, and to point this with data from the studies concerning directly the identification of the persons with technical talent. Theoretical information will support the development and validation of an instrument able to identify the technical talent among the students. That is the auto-nomination inventory of talent in the technical area, the evaluation and validation process of which we'll submit in this study.